Pengaruh Tingkat Upah, Tenaga Kerja dan Modal Kerja Terhadap Produksi Industri Pakaian Jadi Tekstil di Kota Denpasar - M Arsha, I Made Risma; Suardikha Nata, Ketut (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2013)
Textile industry is one sector that has a very rapid development and impact on employment and support is one of Bali's tourism sector. The industry demand continues to increase as it is one of the basic needs of society. The purpose of this study was to determine the influence of the level of wages, hours and working capital either simultaneously or partially to the production of Textile industry in the city of Denpasar. The population was all over the Textile industry in the city of Denpasar, and the owners of the Textile industry as a sample. Using Slovin formula and stratifiled proportionale random sampling techniques, obtained a total sample of 84 employers. The collected data is processed by multiple linear regression analysis. The results showed that simultaneous wage rates, hours of work, and working capital affect the production of the apparel industry with F of 41.216 and 0.000 sig. While partially obtained results that the wage rate is 3,777 t, t obtained working hours and working capital 4,189 5,856 t is the effect on the production of the Textile industry
Keywords: Wage Rates; Hours of Work; Working Capital; Production Textile Garment Industry